Reconstruction of optical pulse intensity and phase based on SPM spectra measurements in microstructured tellurite fiber in telecommunication range - Anashkina, Elena A.; Koptev, Maxim Y.; Andrianov, Alexey; Dorofeev, Vitaly V.; Singh, Surinder; Lovkesh; Leuchs, Gerd; Kim, Arkady (Journal of Lightwave Technology, 2019)
We report novel functionalities of a very simple, robust, and low-cost opticalmetrology method for the reconstruction of an intensity profile and phase of pulses in the telecommunication range based on measuring the fundamental spectrum and two self-phase modulated spectra after a nonlinear element with Kerr nonlinearity. We demonstrate, for the first time, to the best of our knowledge, the possibility of implementing this method using a microstructured tellurite fiber (with a zero dispersion wavelength of 1.55 μm and nonlinear coefficient >500 (W km)-1) as a nonlinear element for characterizing optical pulses with a wide range of parameters: wavelengths from O-band to L-band, durations from <100 fs tõ100 ps, low energies (&tild;100 pJ), and/or low peak powers (&tild;1 W). The intensity and phase of 80-fs ultrashort pulses with an energy of &tild;100 pJ are retrieved experimentally. We give a detailed theoretical analysis of the possibilities of reconstructing telecommunication pulses, including the important problem of measuring two coherent neighboring pulses whose wings may overlap.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Kerr nonlinearity; Optical metrology; Phase reconstruction; Self-phase modulation; Telecommunication pulses; Tellurite fiber